Design of A Thermoelectric Generator for Battery Charging using Heat from A Steam Iron Base - Sundari, Delta; Manfaluthy, Mauludi; Pratama, Legenda Prameswono; Dionova, Brainvendra Widi; Vresdian, Devan Junesco; Putri, Arisa Olivia; Al-Humairi, Safaa Najah Sahud; Mohammed, M. N. (P3M Politeknik Negeri Banjarmasin, 2024)
This study explores an alternative method of generating electrical energy using a thermoelectric generator that utilizes heat from the soleplate of a steam iron and six thermoelectric units connected in series. Based on the Seebeck effect, the thermoelectric modules convert the temperature difference into voltage. An increase in the heat source temperature leads to higher voltage production by the series-connected thermoelectric modules, although the electrical power output depends on the connected load. The power generator design includes thermoelectric modules, a buck-boost converter, an 18650 lithium-ion battery, and a 5-watt, 12-volt DC lamp. The study addresses key aspects such as the impact of temperature on power output in series-connected and parallel-connected thermoelectric circuits, and the efficient conversion of heat from the steam iron soleplate into electrical energy. The research objectives are threefold: to determine power and temperature values for series-connected thermoelectric circuits, to evaluate power and temperature values for parallel-connected thermoelectric circuits, and to utilize heat from the steam iron soleplate as a thermoelectric heat source for generating electrical energy. Testing involved a buck-boost converter connected to a battery, producing 12.35 volts with a temperature difference of 49°C. Design enhancements, such as integrating heatsinks or coolers on the cold side of the modules to maintain a significant temperature differential, are critical for optimizing performance.